2014
DOI: 10.1111/cea.12310
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced bronchospasm related to different phenotypes of rhinitis without asthma in primary schoolchildren: the French Six Cities Study

Abstract: In this large (6813) sample of 10-year children drawn from the general population, EIB is associated with rhinitis phenotypes in the absence of asthma. Furthermore, it constitutes an entity independent from asthma and is not related to a familial history of asthma. Thus, investigating these symptoms could be important in this disease, as a specific nasal treatment might improve EIB in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…1 ). 20 22 , 24 39 There is large variation in the prevalence of EIB in children worldwide, with studies conducted in Nigeria, 25 Brazil 30 and Poland 29 reporting higher rates of EIB than Ghana, 24 India 40 and Greece 26 (Fig. 1 ).…”
Section: Definition and Prevalencementioning
confidence: 99%
See 3 more Smart Citations
“…1 ). 20 22 , 24 39 There is large variation in the prevalence of EIB in children worldwide, with studies conducted in Nigeria, 25 Brazil 30 and Poland 29 reporting higher rates of EIB than Ghana, 24 India 40 and Greece 26 (Fig. 1 ).…”
Section: Definition and Prevalencementioning
confidence: 99%
“…1 Country-specific prevalence* of EIB in children (general population). 20 22 , 24 39 *Owing to differences in study methodology, comparisons between studies should be treated with caution. EIB exercise-induced bronchoconstriction …”
Section: Definition and Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Mounting studies have demonstrated that bronchial provocation test (BPT) played an important role in diagnosing asthma [11,12]. In clinical application, BPT is severed as the gold standard of asthma, especially cough variant asthma (CVA).…”
Section: Introductionmentioning
confidence: 99%